1990
DOI: 10.1159/000174653
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction in Women

Abstract: Cardiovascular disease is the leading cause of mortality in the United States regardless of gender. Women infrequently present with myocardial infarction as the initial presentation of coronary heart disease and have unrecognized infarctions more frequently than men. Myocardial infarction in women has a similar clinical presentation as in men, with the exception of an increased incidence of non-Q wave myocardial infarctions. Complications of acute infarction in women are probably similar although the majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 56 publications
1
6
0
1
Order By: Relevance
“…Overall findings of the sociodemographic and clinical characteristics of the sample in this study demonstrate that this sample was similar to that of other published studies (Dittrich, Gilpin, Nicod, 1988;Greenland, 1991;Hamilton & Seidman, 1993;Hendel, 1990;Kannel & Abbott, 1987;Maynard, 1991;Moser & Dracup, 1996). Thus we can conclude that no obvious bias was introduced in our sampling.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall findings of the sociodemographic and clinical characteristics of the sample in this study demonstrate that this sample was similar to that of other published studies (Dittrich, Gilpin, Nicod, 1988;Greenland, 1991;Hamilton & Seidman, 1993;Hendel, 1990;Kannel & Abbott, 1987;Maynard, 1991;Moser & Dracup, 1996). Thus we can conclude that no obvious bias was introduced in our sampling.…”
Section: Discussionsupporting
confidence: 90%
“…Development of complications is largely responsible for the 10 15% mortality rate in the early stage of AMI (Shah et al, 1994;Swan, 1991). Left ventricular dysfunction (Hendel, 1990), atrial fibrillation (Henning, 1975;Kannel & Abbott, 1987), supraventricular tachycardia (Henning, 1975), left bundle branch block (Henning, 1975), atrioventricular block (Tofler et al, 1987), recurrent ischemia, and reinfarction are common complications associated with in-hospital death.…”
Section: Discussionmentioning
confidence: 99%
“…When women present with AMI, they typically are different than men in a number of characteristics including age, marital status, education level, income, and presence of comorbidities (30,(33)(34)(35). Investigators have suggested that these differences may explain gender differences in anxiety after AMI.…”
Section: Gender Differences In Anxiety After Amimentioning
confidence: 99%
“… 3,4 Previous studies have concluded that there is no strong basis for the assumption that data derived from studies on men with heart disease can be extrapolated to women. 5,6 …”
Section: Introductionmentioning
confidence: 99%